Note on the genus Morimospasma Ganglbauer with description of two new species from China (Coleoptera: Cerambycidae: Lamiinae) - Xie, Guanglin; Zou, Xia; Wang, Wenkai (Zootaxa, 2014)
The genus Morimospasma Ganglbauer, 1890 is reviewed. Two new species, M. jiangi sp. nov. and M. dalaolingensis sp. nov., are described and illustrated. M. paradoxum Ganglbauer is newly recorded from Anhui, China. Taxonomic status of M. nitidituberculatus Hua is discussed. The Chinese names of M. jiangi sp. nov. and M. dalaolingensis sp.nov. are designated, respectively, as Jiǎngshì Jùliútiānniú and Dàlǎolǐng Jùliútiānniú in Chinese phonetic alphabet. A key to all six species of Morimospasma is provided.